Progressive role of artificial intelligence in treatment decision-making in the field of medical oncology - Bongurala, Archana Reddy; Save, Dhaval; Virmani, Ankit (Frontiers in Medicine, 2025)
This article explores the role of artificial intelligence (AI) in medical oncology, emphasizing its impact on treatment decision-making for adult and pediatric cancer care. AI applications, including advanced imaging, drug discovery, and clinical decision support systems, enhance precision, personalization, and efficiency. Pediatric oncology benefits from improved diagnostics, risk stratification, and targeted therapies, despite unique challenges. AI-driven personalized medicine optimizes treatment strategies, improving patient outcomes and reducing costs. Ethical considerations, such as data privacy, algorithmic bias, and explainability, remain critical for responsible AI integration. Future advancements, including explainable AI and quantum computing, promise to redefine cancer care through data-driven insights.